Association between pregnancy intention and preconception health behaviors. Issue 3 (11th October 2021) - Din, Hena Naz; Strong, David; Singh‐Carlson, Savitri; Corliss, Heather L.; Hartman, Sheri J.; Madanat, Hala; Su, H. Irene
Abstract : Background: Female adolescent and young adult (AYA) cancer survivors face higher infertility and pregnancy risks than peers with no cancer history. Preconception health behaviors such as physical activity (PA), tobacco smoking, and alcohol intake influence reproductive outcomes. In general populations, pregnancy intention is positively associated with healthy preconception behaviors, but it has not been studied among AYA survivors. The authors hypothesized that higher pregnancy intention would be associated with healthier behaviors, especially among AYA survivors with perceived infertility risk. Methods: A cross‐sectional analysis was conducted with data collected between 2013 and 2017 from 1071 female AYA survivors aged 18 to 39 years who had completed their primary cancer treatment and enrolled in an ovarian function study. Self‐reported intention dimensions were measured as a pregnancy intention score (PIS) and trying now to become pregnant. Multivariable linear (PA), binary (smoking), and ordinal (alcohol use) logistic regressions were used to estimate associations between intentions and preconception behaviors, with adjustments made for demographic and cancer characteristics. Effect modification by perceived infertility risk was assessed. Results: The mean PIS was 1.1 (SD, 0.77) on a 0 to 2 scale (2 = high intention), and 8.9% were attempting pregnancy now. A higher PIS was associated with increased PA (β, 0.08; 95% CI, 0.11‐1.04), whereas ambivalence in pregnancy intention was associated with lower alcohol consumption (odds ratio, 0.72; 95% CI, 0.55‐0.95). Pregnancy intentions were not associated with smoking. Perceived infertility risk strengthened the relationship between PIS and PA ( P < .05). Conclusions: Pregnancy intentions were associated with some healthier preconception behaviors in AYA survivors. Medical professionals caring for AYA survivors may consider pregnancy intention screening to guide conversations on preconception health. Abstract : Pregnancy intention is positively associated with preconception physical activity and negatively associated with alcohol consumption among female adolescent and young adult cancer survivors. Survivors who feel themselves at risk of infertility engage in more physical activity than survivors with no perceived infertility risk.